2020
DOI: 10.1007/jhep02(2020)167
|View full text |Cite
|
Sign up to set email alerts
|

Gravity edges modes and Hayward term

Abstract: We argue that corner contributions in gravity action (Hayward term) capture the essence of gravity edge modes, which lead to gravitational area entropies, such as the black hole entropy and holographic entanglement entropy. We explain how the Hayward term and the corresponding edge modes in gravity are explained by holography from two different viewpoints. One is an extension of AdS/CFT to general spacetimes and the other is the AdS/BCFT formulation. In the final part, we explore how gravity edge modes and its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 89 publications
4
65
0
Order By: Relevance
“…Interestingly, in some of these cases, we can write down the vacuum wave functions explicitly. Therefore, it might be interesting to compare further these results with the ones for gravity theory where we have universal local correlations, so-called gravity edge modes [63]. Our result may also imply that the quantum corrections of holographic theories can be non-positive.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, in some of these cases, we can write down the vacuum wave functions explicitly. Therefore, it might be interesting to compare further these results with the ones for gravity theory where we have universal local correlations, so-called gravity edge modes [63]. Our result may also imply that the quantum corrections of holographic theories can be non-positive.…”
Section: Discussionmentioning
confidence: 61%
“…Since the boundary is fixed previously, the corner angle is arbitrarily fixed and the Hayward term is required to get a well posed variational problem. In a very recent article [15] Takayanagi and Tamaoka drew attention to a possible application of this term to holographic context and to the study of the entanglement entropy; in particular, using a replica trick calculation close to the Fursaev's approach [5], they showed that the von Neumann entanglement entropy can be explained by considering the Hayward term in the gravitational action. The aim of the present work is to generalize this result to the Rényi entropies, precisely by showing that the cosmic brane term is explained in the own gravitational theory through a Hayward term.…”
Section: Introductionmentioning
confidence: 99%
“…While it did not seem to play an important role in our discussion, a Hayward term might need to be included [45] (for recent work, see e.g. [46]). A thorough analysis could lead to an extended holographic dictionary between bulk modes and fields localized on the brane.…”
Section: Discussionmentioning
confidence: 99%